Relationship between Independent Learning and Learning Achievement of Students in Grade VII of St. Theresia Catholic Junior High School in Kupang in the 2024/2025 Academic Year - Nana, Claudius Robert; Margaretha, Dhiu; Bone, Matilda Pia (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to determine the relationship between learning independence and the academic achievement of seventh-grade students at Sta. Theresia Catholic Junior High School in Kupang City for the 2024/2025 academic year. This study uses a quantitative descriptive research design. The variables in this study are the independent variable (X) of learning independence and the dependent variable (Y) of academic achievement. Data collection instruments used learning independence questionnaires and document studies. Data analysis used the Pearson correlation technique and was processed using SPSS version 26 for Windows. The results of the research data analysis showed a correlation coefficient of 0.522. This means that there is a relationship between learning independence and student achievement.